2013
DOI: 10.1111/iwj.12187
|View full text |Cite
|
Sign up to set email alerts
|

Surgical debridement to optimise wound conditions and healing

Abstract: Different treatment strategies are available for bone, joint and soft tissue infections, including use of local antibiotics; negative pressure wound therapy; one‐stage, two‐stage or multi‐stage revisions; or open wound therapy. All methods have one principle in common: adequate surgical debridement is the prerequisite for successful treatment of bone, joint and soft tissue infections. According to the different textures of healthy, infected or necrotic tissue, special techniques are used. In this article we wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 6 publications
0
7
0
2
Order By: Relevance
“…Aggressive surgical debridement is a useful tool to reduce the risk of soft tissue complications after acute soft tissue infections. 10 Surgery is the treatment of choice in organized hematoma. Organized chronic hematoma has a negative effect on wound healing for leg ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive surgical debridement is a useful tool to reduce the risk of soft tissue complications after acute soft tissue infections. 10 Surgery is the treatment of choice in organized hematoma. Organized chronic hematoma has a negative effect on wound healing for leg ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…The wound was repeatedly ushed after removal of the branch, removal of the granulation and hardening of the bones. Considering that the cause of the infection had been removed, to reduce the patient's pain and the number of operations, we used bone cement with antibiotics to ll the cavity [8,9].…”
Section: Third Operationmentioning
confidence: 99%
“…In 2000, Attinger stated that, after a thorough patient assessment, the most important step to treating any wound is sufficient debridement to remove all foreign material, unhealthy, or non‐viable tissue until the wound edges and base consist of only normal and healthy tissue . In 2013, Diefenbeck concluded that adequate surgical debridement is the prerequisite for the successful treatment of skin, soft tissue and bone tissue . Goss et al reported that surgical wound debridement is necessary before treating infected wounds with NPWTi‐d .…”
Section: Clinical Approach Flow Diagrammentioning
confidence: 99%